The Impact of Selling and Administrative Expenses on Corporate Stock Price Performance - Joseph T. Musandiwa; Collins C Ngwakwe (Облік і фінанси)
Selling costs are vital in shaping a company's profitability position and competitiveness in the market environment, resulting in investor perceptions and also stock price performance. Previous studies indicate that sales costs significantly affect profitability, while profitability mediates stock price performance. High general and administrative (G&A) expenses also may have a significant influence on a company's stock price performance, as controlling them can be a serious problem for any business. This paper moves slightly away from the traditional analysis of selling and administrative expenditure and profitability by evaluating the effect of selling and administrative expenses on corporate share price. Researchers applied a quantitative technique with case data on Woolworths Holdings Ltd (2004 to 2024). Data were collected from the archives of Woolworths Holdings Ltd (for S&D expenses) and Investing.com archives (for stock market price). The results of a simple regression analysis indicate that selling and administrative expenses have a significant and positive effect on the movement of Woolworth's stock price at a p-value of 0.001 over the twenty-one years of data examined in this paper. Hence, the paper offers new insight into the important role of selling and administrative investment beyond the current year of operation and the bottom line. The paper provides practical implications for businesses, including the need for managers to invest efficiently in strategic areas such as current-year adverts and promotions, as these may have multiple years of economic benefits for the company. Theoretically, the result also indicates that the current year's expense values may not be limited to the bottom line and that these expenses may cautiously be included in the variables for economic value-added analysis given their ripple benefit effect unto subsequent years' economic values.